Genome-Wide Analysis of DoSPX Genes and the Function of DoSPX4 in Low Phosphorus Response in Dendrobium officinale - Liu, Lin; Xiang, Haoxin; Song, Jingjing; Shen, Huimin; Sun, Xu; Tian, Lingfeng; Fan, Honghong (Frontiers in Plant Science, 2022)
Phosphorus is one of the vital nutrient elements affecting plant growth and development. The SPX family plays an essential role in the complex regulatory network of phosphorus metabolism in plants. Dendrobium officinale Kimura et Migo is a famous medicinal plant of Orchidaceae with solid adaptability to low phosphorus. In this paper, 9 SPX family genes were identified in the D. officinale genome. Bioinformatics and qRT-PCR analysis showed that DoSPX were involved in plant response and had different spatial and temporal expression patterns. DoSPX4 had a unique expression pattern. The expression level of DoSPX4 reached a peak on 5 d in roots while showing a downward trend in aboveground parts under low phosphorus treatment. DoSPX4 is located on the cell membrane. The Yeast two-hybrid results showed that DoSPX4 could interact with Phosphate High-Affinity Response factor DoPHR2. Overexpression of DoSPX4 in N. tabacum promoted phosphorus content in the stem and the expression level of NtPHT1/2. These results highlight the role of DoSPX4 in response to low phosphorus, which provides a theoretical basis for further study on the response mechanism of low phosphorus in D. officinale.